MLC1 protein: a likely link between leukodystrophies and brain channelopathies - Brignone, Maria S.; Lanciotti, Angela; Camerini, Serena; De Nuccio, Chiara; Petrucci, Tamara C.; Visentin, Sergio; Ambrosini, Elena (Frontiers in Cellular Neuroscience, 2015)
Megalencephalic leukoencephalopathy with subcortical cysts (MLC) disease is a rare inherited, autosomal recessive form of childhood-onset spongiform leukodystrophy characterized by macrocephaly, deterioration of motor functions, epileptic seizures and mental decline. Brain edema, subcortical fluid cysts, myelin and astrocyte vacuolation are the histopathological hallmarks of MLC. Mutations in either the MLC1 gene (>75% of patients) or the GlialCAM gene (<20% of patients) are responsible for the disease. Recently, the GlialCAM adhesion protein was found essential for the membrane expression and function of the chloride channel ClC-2 indicating MLC disease caused by mutation in GlialCAM as the first channelopathy among leukodystrophies.. These results may explain the phenotypic convergence of ClC-2 KO mice showing brain edema and myelin vacuolation and human MLC pathology, despite mutations in the ClC-2 gene were not found in patients affected by this leukodystrophy. On the contrary, the function of MLC1 protein, which binds GlialCAM, its functional relationship with ClC-2 and the molecular mechanisms underlying MLC1 mutation-induced functional defects are not fully understood yet. The human MLC1 gene encodes a 377-amino acid membrane protein with eight predicted transmembrane domains which shows very low homology with voltage-dependent potassium K+ channel subunits. The high expression of MLC1 in brain astrocytes contacting blood vessels and meninges and brain alterations observed in MLC patients have led to hypothesize a role for MLC1 in the regulation of ion and water homeostasis. Recent studies have shown that MLC1 establishes structural and/or functional interactions with several ion/water channels and transporters and ion channel accessory proteins, and that these interactions are affected by MLC1 mutations causing MLC. Here, we review data on MLC1 functional properties obtained in in vitro and in vivo models and discuss evidence linking the effects of MLC1 mut